Protocol for evaluating the role of a gene in protecting mouse retinal ganglion cells - Xinzheng Guo (Elsevier, 2021)
Summary: The degeneration of retinal ganglion cells (RGCs) leads to irreversible vision loss in a variety of pathological states. Here, we describe a protocol to evaluate the role of a gene in protecting mouse RGCs when they sustain injuries from excitotoxicity or axonal damage. This protocol includes the procedures for gene transfer through AAV intravitreal injection, induction of RGC injuries by NMDA-induced excitotoxicity or optic nerve crush, and retina immunohistochemistry to assess RGC survival.For complete details on the use and execution of this protocol, please refer to Guo et al. (2021).